Implementation of a constitutive model for different annealed superelastic SMA wires with rhombohedral phase. (September 2017) - Rigamonti, Daniela; Nespoli, Adelaide; Villa, Elena; Passaretti, Francesca
Highlights: A one-dimensional numerical model is presented to signify the R-phase in NiTi wires. Choosing the phenomenological parameters allows modulating the representation. The peculiar mechanical cycle of NiTi wires in near as drawn condition is modeled. The case of coupling of differently annealed NiTi samples is also modeled. Abstract: Two aspects of NiTi are the focus of the present work. First, the austenite-rhombohedral transformation, which is often neglected by reason of its little mechanical relevance, but can be used in some applications. Second, the superelastic behavior related to a NiTi material that undergoes a low temperature annealing. Driven by the need to have a design tool for an application that uses materials with these characteristics, a model to simulate the pseudoelastic cycle has been developed. It includes the transformation kinetics rule originally presented in Zhu and Zhang (2007), which describes the evolution of the phase fraction as a function of stress and temperature with a sigmoidal law. That rule is modified in the present model by introducing in the sigmoidal law a phenomenological parameter to adapt it to different mechanical trends. Moreover, the model accounts for the presence of all three phases computing the volumetric fraction and its evolution. The calibration and validation of the model has been based on uniaxial tensile tests in thermal chamber on two types of NiTi wires, both exhibiting R-phase transformation, but prepared according to different annealing temperatures. In addition, the model was validated also for the parallel coupling of the two types of annealed wires to reproduce a real application.